1987
DOI: 10.3758/bf03197028
|View full text |Cite
|
Sign up to set email alerts
|

Further explorations of the consistency effect in word and nonword pronunciation

Abstract: Three experiments explored the consistency effect in word and nonword pronunciation. All three experiments involved a common second phase in which subjects were required to pronounce a sequence of consistent and inconsistent words and nonwords. The experiments were distinguished by the nature of Phase 1. In Experiment 1, subjects pronounced a sequence of words and nonwords in which all the words were exceptions. In Experiment 2, all the items in this phase were consistent, and in Experiment 3, they were incons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Although MINT may be a regular word according to GPC rules, its spelling-sound relationship is inconsistent with that of its orthographic neighbor, PINT. To the extent that the process of computing phonology from orthography is sensitive to the characteristics of the neighborhood, performance on a regular but inconsistent word like MINT may also be adversely affected. Glushko (1979) did indeed demonstrate longer naming latencies for regular inconsistent words than for regular words from consistent body neighborhoods, though this result was not always obtained in subsequent experiments (e.g., Stanhope & Parkin, 1987).…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Although MINT may be a regular word according to GPC rules, its spelling-sound relationship is inconsistent with that of its orthographic neighbor, PINT. To the extent that the process of computing phonology from orthography is sensitive to the characteristics of the neighborhood, performance on a regular but inconsistent word like MINT may also be adversely affected. Glushko (1979) did indeed demonstrate longer naming latencies for regular inconsistent words than for regular words from consistent body neighborhoods, though this result was not always obtained in subsequent experiments (e.g., Stanhope & Parkin, 1987).…”
mentioning
confidence: 56%
“…To the extent that the process of computing phonology from orthography is sensitive to the characteristics of the neighborhood, performance on a regular but inconsistent word like MINT may also be adversely affected. Glushko (1979) did indeed demonstrate longer naming latencies for regular inconsistent words than for regular words from consistent body neighborhoods, though this result was not always obtained in subsequent experiments (e.g., Stanhope & Parkin, 1987).In 1990, Jared, McRae, and Seidenberg offered a more sophisticated hypothesis that captures aspects of results not handled by previous accounts referring solely to either regularity or consistency. According to Jared and colleagues, the magnitude of the consistency effect for a given word depends on the summed frequency of that word's friends (words with a similar spelling pattern and similar pronunciation) and of its enemies (words with a similar spelling pattern but a discrepant pronunciation).…”
mentioning
confidence: 79%
“…To the extent that the process of computing phonology from orthography is sensitive to the characteristics of the neighborhood, then performance on a regular but inconsistent word like five should also adversely be affected. Glushko did indeed demonstrate longer response times (RTs) for regular inconsistent words than for regular words from consistent neighborhoods, though this result was not always obtained in subsequent experiments (e.g., Stanhope & Parkin, 1987;Taraban & McClelland, 1987; see also Brown, 1987;Patterson & Coltheart, 1987). In all studies manipulating either regularity or consistency, the effect has been shown to be stronger for low-than for high-frequency target items and is often statistically reliable only for the lower frequency words.…”
mentioning
confidence: 92%
“…Many studies have addressed this question in English (e.g., Andrews, 1982Andrews, , 1989Andrews, , 1992Glushko, 1979;Jared, McRae, & Seidenberg, 1990;Parkin, 1982;Seidenberg, Waters, Barnes, & Tanenhaus, 1984;Stanhope & Parkin, 1987;Taraban & McClelland, 1987;Waters & Seidenberg, 1985). On the basis of the frequent observation (e.g., Coltheart, 1978;Parkin, 1982;Waters & Seidenberg, 1985) that words with regular or typical spelling-sound correspondences (such as five) produce shorter naming latencies and lower error rates than words with exceptional correspondences (e.g., give), regularity was originally considered to be the critical variable.…”
mentioning
confidence: 99%
“…These were the following: (a) scaled scores from the reading comprehension subtests from the MAT, Primary 1 and Primary 2, Forms L (in the standardization sample, K-R 20 = .93 for both levels; Prescott, Balow, Hogan, & Farr, 1986); (b) scaled scores from the reading comprehension subtest of the Illinois Goal Assessment Program (IGAP; in a standardization sample, coefficient a = .84; Valencia, Pearson, Reeve, & Shanahan, 1988); (c) teachers' ratings of students' comprehension measured on a 6-point Likert scale (factor loadings with other measures of comprehension from the study sample provided lower bound estimates of reliability, which were .86 for Grade 2 and .68 for Grade 3); (d) time, in hundredths of a second, to read two passages from the Gray Oral Reading Tests-Revised (in the study sample, coefficient a = .92 for Grade 2 and .89 for Grade 3; Weiderholt & Bryant, 1986); and (e) time, in hundredths of a second, to pronounce two lists of pseudowords adapted from Stanhope and Parkin (1987) and Stanovich, Cunningham, and Feeman (1984) (in a study sample, coefficient a = .90 for Grade 2 and .81 for Grade 3). We took the mean of reading times on the two passages and the mean of pronunciation times on the two lists of pseudowords.…”
Section: Individual Differences In Reading Levelmentioning
confidence: 99%